المنهج الإسلامي في الرعاية الاجتماعية - بتقة, ليلى (Sciences de l'Homme et de la Société, 2012)
لقد عني الإسلام بالإنسان كمخلوق ميزه الله تعالى دون سائر الكائنات وحباه بمنه وفضله وأولاه رعايته وتكريمه قبل أن يولد وحتى الممات  حتى عرف الدين الإسلامي بدين الرعاية الاجتماعية فقد جاء لخدمة الإنسان واستدامة نوعه بصلاحه والصلاح المنوّه به ما أراد الله به مجرد صلاح العقيدة وصلاح العمل فحسب بل أراد منه أيضا صلاح أحوال الناس وشؤونهم في الحياة الاجتماعية من خلال مجموع الخدمات الاجتماعية التي تستهدف العقل والروح والنفس والموجهة للفرد والجماعة والمجتمع.  فهذا المقال يوضح معالم المنهج الإسلامي في الرعاية الاجتماعية وفلسفته التي تميزه وتجعله فريدا عن غيره من المناهج والأنظمة الوضعية بالاضافة إلى خصائص المنهج الإسلامي التي جعلت منه بحق دين الرعاية الاجتماعية.    I have my  Islam man as a creature  advantage of Allaah, without other objects, and endowed by His grace and bounty and paid by the care and honor him before he was born and until death even knew Islam a religion of social welfare, he came to the service of man and the sustainability of its kind goodness and righteousnessmentioned by what Allah wants to do just Salah faith and goodwork, but Salah also wanted him to people's lives and their affairsin social life through the total social services that target the mind, spirit and self-directed individual and group and community. Thisarticle outlines the Islamic approach to social care and philosophythat makes it unique and distinguish it from other approaches andsystems status in addition to the properties of the Islamic approach, which made him the right of the religion of social welfare.